Video analysis of jockey fall characteristics in horse racing - Nylund, L. E.; Sinclair, P. J.; Hitchens, P. L.; Cobley, S. (Journal of Science and Medicine in Sport, 2022)
Objectives: To identify characteristics of jockey falls associated with high-risk landings using a modified Equestrian Fall Assessment Instrument. Design: Cross-sectional study. Methods: Video footage of 22 flat and 58 jump racing falls (N=80) which occurred in Great Britain, Ireland, and New Zealand from 2013 to 2018 was systematically analysed using the modified Equestrian Fall Assessment Instrument. Race, horse, and jockey-level factors, including the nature of ground contact (landings), were characterised identifying factors associated with high-risk landings. High-risk landings refer to cases where the jockey's head impacted the ground or where there was potential horse impact on the jockey. A multivariable logistic regression model was applied identifying independent variables associated with high-risk landings. Results: In 79% (63/80) of race falls examined, at least one high-risk landing factor was present. Three independent variables explained 40.3% of variance in high-risk landings. Lower race class (odds ratio 1.5; 95% confidence interval 0.96, 2.39; p=0.054), hanging onto the reins upon ground impact (odds ratio 7.5; 95% confidence interval 1.04, 53.63; p=0.028), and no jockey tuck-and-roll behaviour following ground impact (odds ratio 4.9; 95% confidence interval 1.65, 14.44; p=0.001) were associated with high-risk landings. Conclusions: Jockeys who ride in lower race classes, who hung onto the reins before landing, and who didn't tuck-and-roll during a fall had increased risk of a high-risk landing. Further examination of relationships between race, jockey experience and fall behaviour characteristics upon injury outcomes, and evaluation of potential protective benefits of fall training are required.